Methods For Verification Of Parameters Of Magnetic Field Sensors - Krejčí, Jakub (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2018)
Many new sensors appear at the market and occasionally it is required to test specification given by producer. Usually are given conditions of measurement, but the procedure stays undercover. The aim of this article is to suggest and describe simple and repeatable method for testing of magnetic field sensors and verify parameters of selected sensor.
Keywords: MEMS; sensor; verification; method